8.8k views
0 votes
If the sum of two expressions is 3x+5 and one expression is 5x-7 what is the other expression

User Wim Leers
by
4.5k points

1 Answer

6 votes

Answer:

-2x + 12

Explanation:

If we call our other expression y, we can set up an equation tying together 3x + 5, y, and 5x - 7:


(5x-7)+y=3x+5

Solving for y by subtracting 5x - 7 from both sides will get us the expression we're looking for:


y=3x+5-(5x-7)\\y=3x+5-5x+7\\y=-2x+12

So the other expression in the sum is -2x + 12.

User Dantastic
by
4.6k points